TEACHING METHODS IN THE UNIVERSITY COURSE “BIOPHYSICS” - Gango, Sergei; Pan'kova, Svetlana; Solovyev, Vladimir; Vanin, Alexander; Yanikov, Mikhail (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents some methods and results of experimental teaching biophysics at Pskov State University (Russian Federation). The goal of any university is to train highly qualified specialists. To achieve this aim, the authors suggest following interdisciplinary approach to the educational process. Some topics of the lecture presentations, video clips and demonstration educational experiments as well as examples of computer modelling of biophysical processes are considered. Subjects of the real and virtual biophysical, biological and medical experimental tasks for students working in an educational university physical laboratory are discussed.